Long non-coding RNA NEAT1 promotes multiple myeloma malignant transformation via targeting miR-485-5p/ABCB8 - Yuxiu Xu; Tao Wang; Jiangwei Wan; Dongsheng Ma; Hongyang Zhang; Dongru Cheng; Jing Yang; Meng Wang (Hematology)
Multiple myeloma (MM) is the second most common hematological cancer all over the world. Long non-coding RNA (lncRNA) nuclear-enriched autosomal transcript-1 (NEAT1) have been reported to play important roles in the development and progression of multiple human malignancies like MM. However, the functional role and molecular mechanism of NEAT1 in MM progression still needs more support to identify potential targets of MM. In the present study, we focused on the clinical and biological significance of NEAT1 in MM. We demonstrated that NEAT1 was up-regulated in MM tissues and cell line. NEAT1 silencing significantly inhibited cell proliferation and promoted cell apoptosis in vitro. And we illustrated that miR-485-5p was a direct target of NEAT1 and the effect of down-regulated NEAT1 on MM cells was partially reversed by the miR-485-5p antisense oligonucleotide (ASO-miR-485-5p). Further investigation revealed that ABCB8 directly interacted with miR-485-5p. Similarly, in vivo experiments confirmed that down-regulated NEAT1 inhibited tumor growth and ABCB8 expression. Taken together, our results demonstrate for the first time that NEAT1/miR-485-5p/ABCB8 axis may be a key pathway for the development and progression of MM, and they may provide a novel avenue for targeted therapy.